Regenerative Dentistry in Pakistan: Awareness, Challenges, and Advancements among General Dental Practitioners and Specialists - Khan, Erum; Soomro, Azeem Hussain; Saleem, Muhammad; Siyal, Zahid Hussain; Ali, Sabir; khurshid, Zohaib (European Journal of General Dentistry, 2022)
Objective Regenerative dentistry has developed a revolutionary advancement in dentistry worldwide. However, significant research still needs to be taken to overcome the challenges in Pakistan. The objective of this study is to evaluate the understanding of general and specialist dentists toward different grafts and their resources during surgical procedures.Materials and Methods A questionnaire was disseminated for our survey-based study, emailed the soft copy, and distributed the hard copies among 400 general dental practitioners (GDPs) and specialists throughout Pakistan to evaluate the types of grafts used to cover bone or soft tissue defects. Out of 400 GDPs and dental specialists, 200 participants returned the completed questionnaires.Results Nearly 200 dental surgeons participated from different regions of Pakistan. Most of the GDPs and specialists in Pakistan are not well aware of tissue-engineered grafts and their role in dentistry. The frequency of utilizing a patient's oral fibroblast to generate the collagen is 5.5%. Most of the GDPs are not aware of the resource of bony spicules if utilized which is 49.5%. Consequently, the use of regenerated tissue (oral) grafts is significantly overlooked in Pakistan (p < 0.001).Conclusion Tissue engineering is an extremely encouraging area of reparative biology that attracts the latest innovation in maxillofacial surgery, oral pathology, implantology, cellular and molecular biology, chemistry, and physiology.
Keywords: tissue engineering; repair; regeneration; dental grafts; cell culture; oral lesions